Upaya Meningkatkan Kemampuan Membaca Dan Menulis Menggunakan Media Kartu Kata Bergambar Di TK Santa Maria Fatima Dulipali - Kornelia Rina Witin; Ujang Maulana Yusup (CV. ITTC INDONESIA, 2025)
This study aims to improve early reading and writing skills in young children through the use of illustrated word card media at TK Santa Maria Fatima Dulipali. This classroom action research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of Cycle I indicated an initial improvement in the ability to recognize letters and copy simple words, although issues remained in terms of neatness and consistency in letter formation. In Cycle II, the learning strategy was enhanced through more varied and individualized approaches, resulting in a significant improvement in children's ability to read and write independently. The use of visual media proved effective in capturing attention, facilitating letter-symbol recognition, and fostering children's interest and confidence in literacy activities. Therefore, illustrated word cards can be used as an alternative instructional strategy suited to the developmental characteristics of early childhood to support the enhancement of basic literacy skills.